Prevention of Dermal Abscess Formation Caused by Staphylococcus aureus Using Phage JD007 in Nude Mice - Ding, Bingyu; Li, Qingtian; Guo, Mingquan; Dong, Ke; Zhang, Yan; Guo, Xiaokui; Liu, Qingzhong; Li, Li; Cui, Zelin (Frontiers in Microbiology, 2018)
Aim: In this study, Staphylococcus phage JD007 bactericidal activity and induced immune responses during treatment were assessed in a dermal abscess model. Materials & methods: Dermal abscesses in nude mice were established by injecting a clinical isolate of S. aureus SA325 isolated from the back under-dermal abscess of an in-patient. Results: Phage JD007 was able to inhibit the growth of S. aureus SA325 at MOI=1 or 10, significantly preventing the formation of dermal abscesses. Moderate immune responses were observed in the prevention group through detection of cytokines. Conclusion: Phage JD007 inhibits the formation of dermal abscesses caused by a clinical S. aureus strain in nude mice without robust immune responses.